2004
DOI: 10.1023/b:appt.0000038031.84705.84
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic volume decrease, pH acidification and chloride channel activation during apoptosis requires CD45 expression in HPB-ALL T cells

Abstract: Mitochondrial-perturbating agents such as toxic coumponds induce apoptosis. We note that the loss of CD45 expression in the lymphoblastic leukemia cell line HPB-ALL (HPB45.0) leads to an inhibition of nuclear apoptosis. Our hypothesis is that the absence of CD45 disturbs protein function regulated by a proto-oncogene of the Src family playing a significant role in nuclear apoptosis. In this work we explore the importance of a chloride efflux on DNA fragmentation. The role of tyrosine kinase in the function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The authors suggested that CD45 might inhibit phosphatidylserine redistribution in response to various non-apoptotic signals [107] confirming a possible role for CD45 in the flip-flop process. We also showed that the phosphorylation levels of the chloride channels are considerably inhibited in CD45-cells [97], suggesting the loss of their activation, which is in agreement with the loss of volume and intracellular acidification that are controlled by chloride channels [109]. It is known that the inhibition of Cl-efflux inhibits DNA fragmentation [110].…”
Section: Involvement Of Cd45 In the Regulation Of The Intrinsic Mitocsupporting
confidence: 81%
See 3 more Smart Citations
“…The authors suggested that CD45 might inhibit phosphatidylserine redistribution in response to various non-apoptotic signals [107] confirming a possible role for CD45 in the flip-flop process. We also showed that the phosphorylation levels of the chloride channels are considerably inhibited in CD45-cells [97], suggesting the loss of their activation, which is in agreement with the loss of volume and intracellular acidification that are controlled by chloride channels [109]. It is known that the inhibition of Cl-efflux inhibits DNA fragmentation [110].…”
Section: Involvement Of Cd45 In the Regulation Of The Intrinsic Mitocsupporting
confidence: 81%
“…Deregulation of ion transport in apoptotic cells leads to changes in intracellular ion levels and disrupts enzyme activity. Our results showed a disturbance of ionic homeostasis in CD45-deficient lymphocytes compared to normal lymphocytes [97]. CD45-deficient cells were shown to lose capacity to reduce their cellular volume and intracellular pH acidification after TBT exposure two processes required for DNA fragmentation [104,105].…”
Section: Involvement Of Cd45 In the Regulation Of The Intrinsic Mitocmentioning
confidence: 64%
See 2 more Smart Citations
“…Condensation of ribosomes has been found in apoptotic cells (32) and may explain the altered fluorescence intensity; however, such details could not be resolved in vivo. An altered pH has been described in cells undergoing apoptosis (6), and fluorescent agents such as fluorescein are known to show a pH-dependent fluorescence intensity (27). However, variation of pH from seven to eight in intact liver slices did not result in altered fluorescence, and not all cells becoming dark underwent apoptosis, although apoptosis was always preceded by darkening.…”
Section: Discussionmentioning
confidence: 99%